Pengaruh Corporate Social Responsibility, Profitabilitas, Aktivitas, Reputasi Perusahaan, Dan Ukuran Perusahaan Terhadap Kinerja Keuangan pada Perusahaan Manufaktur Makanan dan Minuman yang Terdaftar di Bursa Efek Indonesia Tahun 2020-2022 - Yoga Gunadarma; Rina Trisnawati (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Financial performance reflects a company's financial condition over a specific period of time based on the capital and capital sources it has acquired. This study aims to analyze the influence of Corporate Social Responsibility, profitability, activities, corporate reputation, and company size on financial performance. The sample used in this study was a food and beverage manufacturing company listed on the Indonesia Stock Exchange in 2020-2022. The sampling method used in this study was purposive sampling according to predetermined criteria, resulting in 58 samples. The data analysis used multiple linear regression techniques. The analysis showed that Corporate Social Responsibility, activities, and company size had no effect on financial performance, while profitability and company reputation did.